SYNTHESIS AND STRUCTURE OF COBALT(II) COMPLEX WITH 2,6-DIACETYLPYRIDINE-BIS(PHENYLHYDRAZONE) - Belošević, Svetlana; Rodić, Marko; Radanović, Mirjana; Leovac, Vukadin (Bulletin of Natural Sciences Research, 2018)
The molecular and crystal structure of a newly synthesized Co(II) complex with 2,6-diacetylpyridine bis(phenylhydrazone) (L), of the formula [CoL2]I2 are described. The reaction of warm EtOH solutions of the ligand, 2,6-diacetylpyridine bis(phenylhydrazone) and CoI2 in molar ratio 1:1 resulted in formation of black single crystals of the title complex. This is the first and so far, the only metal complex with this ligand that is characterized by single crystal X-ray crystallography. Co(II) is situated in a distorted mer-octahedral surrounding of two tridentate N3 coordinated ligand molecules. Complex crystallizes in monoclinic crystal system in C2/c space group. Besides X-ray analysis, conductometric, spectroscopic and magnetic properties of the complex are investigated.